2021
DOI: 10.1055/s-0041-1722945
|View full text |Cite
|
Sign up to set email alerts
|

Use of Emotional and Neutral Speech in Evaluating Compression Speeds

Abstract: Background Emotional speech differs from neutral speech in its envelope characteristics. Use of emotional speech materials may be more sensitive for evaluating signal processing algorithms that affect the temporal envelope. Purpose Subjective listener preference was compared between variable speed compression (VSC) and fast acting compression (FAC) amplitude compression algorithms using neutral and emotional speech. Research Design The study used a single-blinded, repeated measures design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There have been numerous experimental studies on the effect of FAC and SAC hearing aids. The majority of the studies reported that the sound quality of SAC hearing aids is generally preferred over FAC hearing aids (Korhonen et al, 2021). The results are mixed when speech recognition was considered.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous experimental studies on the effect of FAC and SAC hearing aids. The majority of the studies reported that the sound quality of SAC hearing aids is generally preferred over FAC hearing aids (Korhonen et al, 2021). The results are mixed when speech recognition was considered.…”
Section: Introductionmentioning
confidence: 99%